3D model reconstruction and analysis of athletes performing giant slalom - Meyer, F.; Borrani, F. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Nowadays, giant slalom races are won by hundredths of a second. Difference between the athletes on the podium is generally less than 0.5 s, which represent less than 0.5% on a 2 min race. Very small details make the difference and it is important to understand where, when and how the top athletes make the difference. Energy principles in slalom have already been explored (Kugovnik 2005, Reid 2009), but giant slalom biomechanics still needed to be explored. The aim of this project was to develop a system adapted to giant slalom analysis and to figure out the possibility for an athlete to increase his energy, and therefore improve his time, through active movements during turns.